Розробка систем розпізнавання голосових команд - Зіміна, А. Р. (ХНУРЕ, 2019)
The given work is devoted to the development of modern system for speech recognition and voice commands. Speech recognition technologies are used for voice commands, in situations where speaking is much easier than typing. Speech recognition is used in interactive language self-service systems, for example, when a telephone is used by a robot that can deal with standard support questions. Another application of voice recognition technologies is dictation of texts, a kind of automatic secretary, which can be useful for people with disabilities. Finally, systems with voice control, with any kind of technique, such as "smart home", or a car, are increasingly appearing. The developed software can be used to recognize the language and dictate text, for example, for people with disabilities